Peran Bimbingan Konseling Islam dalam Mengatasi Kenakalan Remaja - Anisya Afifa; A. Abdurrahman (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This article discusses the role of Islamic counseling guidance in overcoming juvenile delinquency. The method used is descriptive analysis, namely by exploring all sources related to Islamic counseling guidance as an effort to overcome juvenile delinquency. The data collection technique used in this research is library research where library research is the activity of collecting data or materials related to research through books, scientific journals, literatures and other publications that can be used as sources for research that will be carried out. researched by the author. The purpose of the study was to eradicate the problem of juvenile delinquency with Islamic counseling guidance. In adolescence, they want to show their existence and not infrequently they want to get recognition or want to be considered their existence in the midst of society by doing various things, both positive and negative things which is commonly called juvenile delinquency. Juvenile delinquency is a serious problem that must be addressed immediately in order to save the next generations of the nation. Islamic counseling guidance is one of the efforts that can be used in overcoming delinquency in adolescents, where Islamic counseling guidance aims to help individuals realize themselves into complete human beings in order to achieve happiness in life in the world and in the hereafter in accordance with Islamic laws. So it is hoped that later with the Islamic counseling guidance method, juvenile delinquency can be eradicated and not only that but also can form a better person according to religious norms and form quality teenagers who are religiously obedient.